1998
DOI: 10.1001/archneur.55.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Functional Brain Imaging in Apraxia

Abstract: Background: An extensive literature describes structural lesions in apraxia, but few studies have used functional neuroimaging. We used positron emission tomography (PET) to characterize relative cerebral glucose metabolism in a 65-year-old, right-handed woman with progressive decline in ability to manipulate objects, write, and articulate speech.Objective: To characterize functional brain organization in apraxia. Design and Methods:The patient underwent a neurological examination, neuropsychological testing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(6 citation statements)
references
References 49 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Foster et al [26] reported evidence of right parietal lobe activation detected in AD patients when performing a limb apraxia imitation task. Further evidence of a largely distributed network is provided by the PET findings in a patient with left fronto-parietal dysfunction who showed preserved gesture comprehension [31].…”
Section: Discussionmentioning
confidence: 95%
“…Foster et al [26] reported evidence of right parietal lobe activation detected in AD patients when performing a limb apraxia imitation task. Further evidence of a largely distributed network is provided by the PET findings in a patient with left fronto-parietal dysfunction who showed preserved gesture comprehension [31].…”
Section: Discussionmentioning
confidence: 95%
“…A functional neuroimaging study of a patient with apraxia using fludeoxyglucose F 18 positron emission tomography (PET) reported focal reductions of glucose metabolism in the left angular gyrus and left supramarginal gyrus. 27 Heilman and colleagues proposed a model of ideomotor apraxia in which the movement formulae for ideomotor praxis are stored in the left inferior parietal lobule based on lesion data. 13 Our finding fits well with a recent lesion study using computed tomography (CT) and MRI by Haaland and colleagues, who found maximal overlap of lesions in patients with ideomotor apraxia in the left intraparietal sulcus.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty two (20 men and two women) young, right handed, healthy subjects were examined (mean age, 22.9 years; SD, 3.70; range, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Handedness was assessed by the Edinburgh inventory (mean, 97; SD, 4.8; range, 84-100).…”
Section: Subjectsmentioning
confidence: 99%
“…Moll et al [33] reported that functional MRI during gesture performance in neurologically intact individuals revealed activation in left frontal and parietal regions, including the dorsolateral frontal and intraparietal cortex [33]. Kareken et al [41] performed a positron emission tomography (PET) study of a 65-year-old woman with progressive neurologic deficits including apraxia and showed reduced uptake in left frontal (supplementary motor area) and parietal (angular gyrus, supramarginal gyrus) regions [41]. …”
Section: Anatomy Of Ideomotor Limb Apraxiamentioning
confidence: 99%
“…Support for this anterior-posterior dissociation has come from lesion studies showing impaired gesture recognition after posterior, but not anterior, left hemispheric injury [22]. Imaging studies have less consistently shown such a relationship [15,41,47]. …”
Section: Neuropsychological Models Of Apraxiamentioning
confidence: 99%